Sasa veitchii Extract Mitigates Mycophenolate Mofetil-Induced Human Palatal Cell Proliferation Inhibition by Downregulating microRNA-4680-3p - Hanane Horita; Yosuke Tsukiboshi; Kenichi Ogata; Aya Ogata; Hisaka Kurita; Shuji Yamashita; Hirotaka Yamashita; Naoki Inagaki; Hyogo Horiguchi; Hiroki Yoshioka (Plants)
Cleft palate is a common birth defect worldwide and is caused by both genetic and environmental factors. Intrauterine drug exposure is one of the environmental factors that can induce cleft palate. Mycophenolate mofetil (MPM) is an immunosuppressant drug with teratogenic effects, including cleft palate. However, the research on MPM-induced cleft palate remains limited. Sasa veitchii extract (SE), a medical plant extract, is commercially available in Asia and has been reported to show effectiveness against oral diseases. The purpose of the present study is to evaluate whether SE protects against MPM-induced immunosuppression in human embryonic palatal mesenchymal (HEPM) cells. Cell viability and G1 phase-related cell cycle markers were assessed by co-treatment with MPM and SE. Furthermore, we quantified cleft palate-associated miRNA levels and the expression of its downstream genes. MPM treatment reduced cell viability in a concentration-dependent manner. Co-treatment with SE alleviated MPM-induced inhibition of HEPM cell proliferation. Additionally, SE reduced MPM-induced miR-4680-3p upregulation and the downregulation of its downstream genes (ERBB2 and JADE1). These results suggest that SE alleviated MPM-induced cell proliferation inhibition through modulating miR-4680-3p expression.